Pediatric oral pulse granuloma: A rare entity - Saraswathi Vishnu Naik; Syed Ghousia; Kamalaksharappa Shashibhushan; Deepa Benni (Wolters Kluwer Medknow Publications, 2012)
A pulse granuloma is nothing but a reaction of the foreign body to any vegetable which is characterized by a collection of the hyaline; a hyaline is a transparent substance that is formed from the pathological degeneration of the tissue. These granulomatous rings may be oral or extra-oral. It is important to recognize such a type of granuloma because it may resemble serious pathological processes or may clinically stimulate neoplasia. It might also be confused morphologically with hyaline vasculopathy. The following manuscript presents a rare case of oral pulse granuloma. As going by the literature-search, the following being the only case to have been occurred in a pediatric patient. The authors therefore aim to bring awareness amongst the pediatric dentists about its etiology, occurrence, clinical features and thereby management of the same.